Impact of prosthodontic rehabilitation on the masticatory performance of partially dentate older patients: Can it predict nutritional state? Results from a RCT. (January 2018) - Wallace, Sara; Samietz, Stefanie; Abbas, Meriem; McKenna, Gerald; Woodside, Jayne V; Schimmel, Martin
Abstract: Objectives: With a decreased number of teeth, a reduction in chewing function can contribute to changes in food choices and ultimately impact on overall nutritional status. This study compared the impact of two tooth replacement strategies for partially dentate older patients on masticatory performance and nutritional status. Methods: Patients aged 65 years and older were randomly allocated to two different treatment groups. For the RPDP-group (removable partial dental prostheses) each participant was restored to complete dental arches with cobalt-chromium removable prostheses. For the SDA-group (shortened dental arch), participants were restored to 10 occluding pairs of natural and replacement teeth using adhesive bridgework. Masticatory performance was assessed with a colour-mixing ability test. Each patient provided haematological samples that were screened for biochemical markers of nutritional status. Patients were also assessed using the Mini Nutritional Assessment (MNA). Results: Eighty-nine patients completed the test for masticatory performance and provided blood samples and MNA scores at baseline (BL) and after 12 months (12 m). Masticatory performance (p < 0.001) and MNA (p < 0.05) increased significantly in both groups, but no significant between group differences were noted. A mixed picture was observed for nutrition biomarkers. Mixed-effect linear regression models did not demonstrate that nutritional status could be predicted from masticatory performance. Conclusions: These results indicate that prosthodontic rehabilitation according to the principles of the SDA is equivalent to RPDPs in terms of restoration of chewing capacity for partially dentate older patients. However, masticatory performance may only have minor associations with nutritional status for this patient group. Clinical significance: Replacing teeth with either RPDPs or SDA provides a prerequisite for efficient chewing. Further research is required to determine the impact of oral rehabilitation coupled with nutritional counselling for this patient population.